Building the ecological city - White, Rodney R. (Woodhead ; CRC Press, 2002)
Building the Ecological City puts forward solutions to the question - how can we build cities that provide an acceptable standard of living for their inhabitants without depleting the ecosystems and bio-geochemical cycles on which they depend? The book suggests and examines the concept of urban metabolism which characterizes the city as a set of interlinked systems of physical flows linking air, land, and water. A series of chapters looks at the production and management of waste, energy use and air emissions, water supply and management, urban land use, and air quality issues. Within the broader context of climate change, the book then considers a range of practical strategies for restoring the health of urban ecosystems from the remediation of 'brownfield' land to improving air quality and making better use of water resources.